2022
DOI: 10.1096/fj.202101807r
|View full text |Cite
|
Sign up to set email alerts
|

The Notch pathway regulates the bone gain induced by PTH anabolic signaling

Abstract: Parathyroid hormone (PTH) signaling downstream of the PTH 1 receptor (Pth1r) results in both bone anabolic and catabolic actions by mechanisms not yet fully understood. In this study, we show that Pth1r signaling upregulates the expression of several components of the Notch pathway and that Notch signals contribute to the catabolic actions of PTH in bone. We found that constitutive genetic activation of PTH receptor signaling in osteocytes (caPth1rOt) or treatment with PTH daily increased the expression of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The dose of PTH (100 μg•kg −1 per day or 24 pmol•g −1 per day) was chosen to attain optimal responses based on earlier studies. [39][40][41][42] The dose of ABL (95 μg•kg −1 per day or 24 pmol•g −1 per day) was chosen to allow a direct mole to mole comparison with PTH. Half dose of ABL (47.5 μg•kg −1 per day or 12 pmol•g −1 per day) was also used based on our earlier study with the PTHrP (1-37) and diabetic mice 19 and studies using ABL in ovariectomized rats.…”
Section: Animalsmentioning
confidence: 99%
“…The dose of PTH (100 μg•kg −1 per day or 24 pmol•g −1 per day) was chosen to attain optimal responses based on earlier studies. [39][40][41][42] The dose of ABL (95 μg•kg −1 per day or 24 pmol•g −1 per day) was chosen to allow a direct mole to mole comparison with PTH. Half dose of ABL (47.5 μg•kg −1 per day or 12 pmol•g −1 per day) was also used based on our earlier study with the PTHrP (1-37) and diabetic mice 19 and studies using ABL in ovariectomized rats.…”
Section: Animalsmentioning
confidence: 99%
“…The involvement of the Notch signalling pathway in the osteoblast-Ti interaction is underexplored, despite its well-known participation in osteogenesis [ 31 , 66 , 67 ]. The Ti surface hydrophilicity was observed to favour bone formation by acting on several signalling pathways involved in proliferation and osteoblast precursor differentiation, including Notch signalling [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have reported that prolonged iPTH treatment boosts the expression of Notch pathway components like Notch1 in osteocytes, contributing to a reduced bone resorption and increased bone formation [ 210 ]. The activation of Notch1 promotes the expression of OPG and also inhibits Sost in osteocytes, which increases bone formation [ 211 ].…”
Section: The Direct Interactions Of Pth With Bm Cellsmentioning
confidence: 99%